Immunotoxicity Studies on the Insecticide 2-((1-(4-Phenoxyphenoxy)propan-2-yl)oxy)pyridine (MPEP) in Hsd:Harlan Sprague Dawley SD® Rats - Victor J. Johnson; Stefanie C. M. Burleson; Michael I. Luster; Gary R. Burleson; Barry McIntyre; Veronica G. Robinson; Reshan A. Fernando; James Blake; Donna Browning; Stephen Cooper; Shawn Harris; Dori R. Germolec (Toxics, 2025)
The broad-spectrum insect growth regulator (IGR) and insecticide 2-((1-(4-Phenoxyphenoxy)propan-2-yl)oxy)pyridine (MPEP; also known as pyriproxyfen) is increasingly being used to address public health programs for vector control, initiated by the spread of Zika virus in 2015–2016. While considered relatively safe for humans under normal conditions, limited toxicology data are available. Current studies were undertaken to address the data gap regarding potential immunotoxicity of MPEP, with particular emphasis on host resistance to viral infection. Hsd:Harlan Sprague Dawley SD® rats were treated for 28 days by oral gavage with doses of 0, 62.5, 125, 250 or 500 mg/kg/day of MPEP in corn oil. There was a dose-dependent increase in liver weights which is consistent with the liver playing a dominant role in MPEP metabolism. However, no histological correlates were observed. Following treatment, rats were subjected to a battery of immune tests as well as an established rat model of influenza virus infection to provide a comprehensive assessment of immune function and host resistance. While several of the immune tests showed minor exposure-related changes, evidenced by negative dose–response trends, most did not show significant differences in any of the MPEP treatment groups relative to vehicle control. Most notable was a negative trend in pulmonary mononuclear cell phagocytosis with increases in dose of MPEP. There was also a positive trend in early humoral immune response (5 days after immunization) to keyhole limpet hemocyanin (KLH) as evidenced by increased serum anti-KLH IgM antibodies which was followed later (14 days following immunization) by decreasing trends in anti-KLH IgM and IgG antibody levels. However, MPEP treatment had no effect on the ability of rats to clear the influenza virus nor the T-dependent IgM and IgG antibody response to the virus. The lack of effects of MPEP on host resistance to influenza suggests the immune effects were minimal and unlikely to present a hazard with respect to susceptibility to respiratory viral infection.